Surgical treatment of maxillary transverse deficiency: retrospective study of 14 patients - Contar, Cintia Mussi Milani (Springer-Verlag, 2009)
INTRODUCTION: The diversity of the proposed techniques in the treatment of maxillary transverse deficiency in adults reflects the conflicting opinions about the primary area of resistance to maxillary expansion in the craniofacial skeleton. In order to evaluate the efficiency of the surgical expansion in which no osteotomies of the pterygomaxillary junction were made, we have carried out a retrospective study with 14 patients with maxillary transverse deficiency, who were treated from 2003 to 2006. MATERIAL AND METHODS: In the study, models were made prior to and after surgery, and the intercanine and intermolar distances and the improvement of the interocclusal relationships were analyzed. Breathing function and the complications that occurred during and after the surgeries were also analyzed. RESULTS: All expansions were carried out according to pre-surgical planning so that expansion completely corrected the crossbite, resulting in the desired final occlusion for all patients. Intraoperative complications were limited to one Hyrax appliance deformation. Two patients had minor postoperative complications that included wound dehiscence and pain. Improvements in nasal breathing were observed in all patients that complained of breathing problems prior to the surgery. CONCLUSION: The satisfactory results obtained turns the surgical protocol described in this study recommended for the treatment of maxillary transverse deficiency in adults. Importantly, we found that pterygomaxillary osteotomy is not essential for maxillary expansion. The morbidity of the procedure was low with fairly minor complications, and surgically assisted rapid maxillary expansion was shown to improve nasal breathing.